Tolerability profile of paliperidone palmitate formulations: A pharmacovigilance analysis of the EUDRAVigilance database - Giuseppe Cicala; Renato de Filippis; Maria Antonietta Barbieri; Paola Maria Cutroneo; Pasquale De Fazio; Georgios Schoretsanitis; Georgios Schoretsanitis; Georgios Schoretsanitis; Edoardo Spina; Edoardo Spina (Frontiers in Psychiatry, 2023)
IntroductionLong-acting injectable antipsychotics (LAIs) have proven to be effective in the maintenance treatment of patients suffering from schizophrenia, and their safety and tolerability profiles represent a key factor in their long-term use and choice in clinical practice. Paliperidone palmitate (PP) is the only second-generation LAI (SGA-LAI), available in both one- (PP1M) and 3-month (PP3M) formulations. However, real-world prospective studies on PP1M and PP3M are still few and mostly conducted on small samples. In this context, we aimed to better define the safety and tolerability profile of PP using real world pharmacovigilance data.MethodsWe retrospectively analyzed the publicly available data regarding Individual Case Safety Reports (ICSRs), presenting PP1M and/or PP3M as suspected drugs, reported on EUDRAVigilance between 2011 and June 30th, 2022. ICSRs relative to at least one SGA-LAI other than PP, reported between 2003 and June 30th, 2022, were also examined as reference group. Data were evaluated with a descriptive analysis, and then, as disproportionality measures, crude reporting odds ratio (ROR) and 95% confidence interval (CI) were calculated.ResultsA total of 8,152 ICSRs met the inclusion criteria, of those 77.7% (n = 6,332) presented as suspected drug PP1M, 21.2% (n = 1,731) PP3M, while 89 cases indicated both PP1M and PP3M. Significantly higher probabilities of reporting in PP-related reports were observed for the primary Standardized MedDRA Queries “Sexual Dysfunctions” (ROR = 1.45; 95% CI 1.23-1.70), “Haemodynamic oedema, effusions and fluid overload” (ROR = 1.42; 1.18-1.70), as well as “Fertility disorders” (ROR = 2.69; 1.51-4.80).DiscussionOur analysis indicates that the tolerability and safety profiles of PP are in line with what is known for the other SGA-LAIs. However, differences regarding endocrine system ADRs have been noticed. The results presented in this work do not discourage the prescription of SGA-LAI formulations but aim to enhance their safety.